Essays on immigration and regional economics - Lucchetti, Gabriele (2024)
People have always been on the move, but in recent decades, international migration has reached unprecedented levels. People from all over the world are leaving their homes in search of better lives. Some are fleeing violence or persecution, while others are seeking economic opportunity, family reunification, or simply a new adventure. Whatever their reasons, migrants play an important role in the global economy and society.